Implementasi Sistem Kebijakan Zonasi Pada SD Aisyah Surabaya Kecamatan Genteng Jawa Timur - Aisyah Safira Maharani; Anggraeny Puspaningtyas (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
To improve the quality of education in Indonesia, school reform includes zoning. Minister of Education and Culture Regulation Number 44 of 2019 concerning Admission of New Students to Kindergartens, Elementary Schools, Middle Schools, High Schools and Vocational High Schools is part of the government's efforts to evaluate education. This study aims to explain how the implementation of the Zoning Policy for New Student Admissions is carried out as an effort to check the quality of education in state elementary schools and elementary schools in Genteng District, Surabaya City. The author uses a qualitative consideration literature study method. According to Van Meter and Van Horn in Subarsono (2013: 99), six variables are used as the focus of research: policy size and objectives, resources, characteristics of implementing agents, tendencies or propensities of implementers, communication between organizations and activities, and the economic, social, and politics. Technical data used. The results show that those implementing the Zoning Policy for Admission of New Students as an Effort to Study the Quality of Education (Primary School and Junior High School Level Studies in Genteng District, Surabaya City) have followed the expected policy. Although zoning policies are necessary, there are still some problems. Social, political and economic resource and environmental variables are still difficult to apply.